Pengaruh Gaya Kepemimpinan Transformasional Lingkungan Kerja dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Biro Umum Sekretariat Daerah Provinsi Kalimantan Tengah - Apriyati Apriyati; Lelo Sintani; Achmad Syamsudin; Yunikewaty Yunikewaty; Usup Riassy Christa; Robby Sambung (FKIP, Universitas Palangka Raya, 2022)
This study aims to analyze the effect of leadership style, work environment, and human resource development on employee performance. The method used in this research is explanatory (research explanatory). The sample of this study amounted to 97 people. The data were analyzed using descriptive analysis and statistical inferential analysis of the Structural Equation Modeling (SEM) using the Partial least squares approach (SEM-PLS). The findings in the study conclude that leadership style, work environment, and human resource development have a significant effect on employee performance at the General Bureau of the Regional Secretariat of Central Kalimantan Province. The work environment variable is the variable that has the greatest influence on employee performance. Research implications provide information for policy makers, stakeholders and management to pay attention to a good and well-articulated work environment and HR development in organizations.